(untitled) (Research, Society and Development, 2023)
Botanical phenology aims to observe reproductive and vegetative phenophases, and their causal relationships with abiotic and biotic events, and thus understand, for example, how these occur at the species level and which environmental variables are predominant to achieve each phenophase. In the tropics, there are recurrent studies that use circular statistics to analyze the average data on the occurrence of events, as well as the concentration of these phenological events. The present work aimed to carry out a bibliographic review about the contributions of circular statistics to obtain reproductive phenological data in populations and forest plant communities. For the construction of this research, the inclusion of articles from journals published between 2012 and 2022, in English or Portuguese, made available on the platforms, Portal de Periódicos of the Coordination for the Improvement of Higher Education Personnel (CAPES), was adopted as a selection protocol, SciELO and Google Scholar, which culminated in the incorporation of 13 articles in this study. The results found showed the symbol of circular statistics for the detection, at the population and community level, of the seasonality of reproductive events (in general, flower bud, anthesis, mature and immature fruits), average data on the occurrence of such episodes and your period of concentration. It is also possible to evaluate the interference of climatic phenomena (El Niño) at the time of occurrence of the phenophases. It is concluded that such results can be improved for commercial purposes, understanding of weather events and actions to recover degraded areas.